2011
DOI: 10.2967/jnumed.111.093716
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-Labeled Peptide for PET of Breast Carcinomas Expressing the Thomsen-Friedenreich Carbohydrate Antigen

Abstract: Thomsen-Friedenreich (TF) antigen is a disaccharide, galactose b1-3 N-acetylgalactosamine (Galb1-3GalNAc), expressed on the cell surfaces of most human carcinomas including breast. In this study, we synthesized and evaluated the in vitro and in vivo properties of a 64 Cu-radiolabeled TF antigen-specific peptide derived from bacteriophage display for the purpose of breast tumor targeting and PET of human breast tumors in xenografted mice. Methods: The TF antigen-specific peptide IVWHRWYAWSPASRI was synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Some studies have suggested estimating tumor perfusion from a short dynamic image performed at the time of FDG injection (36). Dual time point imaging has also been tested and may provide additional data on FDG kinetics; (41, 42) however its values may be more limited in low uptake tumors where there is either a slight increase or minimal decrease in SUV over time (40). Further optimization of kinetic analysis measures may yield insights into practical alternatives that overcome the limitations of purely static measures and lead to the establishment of clinical scenarios where optimized kinetic analysis may be the most helpful, as in the case of low baseline tumor FDG uptake (15).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested estimating tumor perfusion from a short dynamic image performed at the time of FDG injection (36). Dual time point imaging has also been tested and may provide additional data on FDG kinetics; (41, 42) however its values may be more limited in low uptake tumors where there is either a slight increase or minimal decrease in SUV over time (40). Further optimization of kinetic analysis measures may yield insights into practical alternatives that overcome the limitations of purely static measures and lead to the establishment of clinical scenarios where optimized kinetic analysis may be the most helpful, as in the case of low baseline tumor FDG uptake (15).…”
Section: Discussionmentioning
confidence: 99%
“…Dual-time-point imaging, with increasing and decreasing 18 F-FDG uptake over time and this indicates breast malignancy and inflammatory lesions, respectively, has been reported to be highly sensitive and specific (7). Nevertheless, our case demonstrated an inflammatory lesion, which was ultimately proven to be a siliconoma (silicone granuloma) caused by silicone injection, and this led to a false positive result owing to a high and persistent increase in 18 F-FDG uptake on the 18 F-FDG PET images.…”
Section: Discussionmentioning
confidence: 99%
“…F-18 FDG uptakes in many malignant lesions are increased with time interval [22, 23]. In patients with ML, recently, Shinya et al [2] statistically evaluated the differences of FDG uptake in early and delayed scans, and compared the maximum SUV (SUVmax) and the retention index (RI) of SUVmax (RI-SUVmax) between the different grades of lymphoma.…”
Section: Introductionmentioning
confidence: 99%